Structural Changes in the Market of Bank Deposits of Households in Ukraine - Kichurchak, Marianna (Journal of Finance and Financial Law, 2021)
The purpose of the article is to identify the main factors that cause the structural changes in the market of bank deposits of households by regions of Ukraine. This is based on evaluating the spatial asymmetries in this market development in 2009–2018 by regions of Ukraine and identifying the factors that influences its structure by gross regional product (GRP) by means of the methodology of multivariate econometric modelling. Methodology. The following scientific methods are used: analysis and synthesis, induction and deduction, comparative analysis and econometric modelling. The scope and coefficients of variation for such indicators as the share of household bank deposits by GRP, the volume of household bank deposits per capita, the structure of household bank deposits by terms in general, in national and foreign currencies are calculated. Determining the main factors for multiple regression equations influencing structural changes in the market of household bank deposits by GRP is based on the methodology of stepwise regression. Results of the research. The spatial peculiarities of household bank deposits development in Ukraine was analysed and the reduction of its capacity was revealed due to the unfavourable socio-economic situation, the reform of the banking system and the influence of geopolitical factors. Based on the assessment of variation indicators dynamics, it was found that this market is characterised by regional asymmetries in terms of types of currencies and placement of household deposits. Regression-correlation equations were built, in which the shares of household deposits by regions of Ukraine (Y1, % GRP), in national currency (Y2, % GRP) and foreign currency (Y3, % GRP) are selected as dependent variables. The following measures are proposed to achieve positive changes in the market of household bank deposits in Ukraine: reducing unemployment; creation of favourable conditions for increasing the average monthly salary in the regions and modifying household spending to make savings; formation of an appropriate interest rate policy aimed at actively attracting temporarily available funds of the population to commercial banks.